Current treatment of post-tonsillectomy pain: a review - Swain, Santosh Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Tonsillectomy is one of the most common surgical procedures performed by an otorhinolaryngologist. This surgery is done more in the pediatric age group. Although tonsillectomy is safe and effective surgery, it is usually associated with significant post-operative pain. Analgesics used for post-tonsillectomy pain is often inadequate. Severe throat pain following tonsillectomy has been documented for decades. Patients or parents/caretakers often worry about such severe pain in the home. The pain following tonsillectomy is usually intense and long-lasting. The severe post-tonsillectomy pain often overstrains the patient, family, and hospital staff. Regular changes in the analgesic armamentarium, particularly in pediatric patients are making the treatment of post-tonsillectomy pain more challenging. Pain following the tonsillectomy period continues to be a highly debated issue and an area of active research. Throat pain in the post-tonsillectomy period can result in significant morbidity among patients. There are different analgesics available; each one has its risk profile and side effects when used for controlling post-tonsillectomy pain. This review article discusses on recent management of post-tonsillectomy pain. This article reviews the epidemiology, pathophysiology, impact of post-tonsillectomy pain, and details of medications used for controlling post-tonsillectomy pain.